A nest of Brown nunlet (Nonnula brunnea) and observations on the nesting of other ecuadorian puffbirds: Un nido de la nonula parda (Nonnula brunnea) y observaciones sobre la anidación de otros bucos ecuatorianos (Ornitología Colombiana, 2021)
The Brown nunlet (N. brunnea) is one of six species of small puffbirds in the genus Nonnula. Here, we describe a nest of Brown Nunlet from Amazonian Ecuador. The nests' architecture iverges from that of other bucconids, built neither in a subterranean burrow nor in a termitarium, but rather is a flattened, dome-shaped structure composed of leaf litter above a shallow depression. Structural integrity of the leafy dome is created with carefully placed sticks and the inner chamber is entered through a short tunnel. We also provide observations that clarify uncertainties in nest placement of White-chested Puffbird (Malacoptila fusca) and observations on the breeding of other Bucconidae in Amazonian Ecuador.